Health Risk Management Practices in Flood-Prone Public Elementary Schools in Caraga Region, Philippines - Cubillas, Ariel U. (International Journal of Membrane Science and Technology, 2023)
This study aimed to profile the flood-prone public elementary schools in Caraga region and identify their health and safety risk management practices. It utilized a descriptive research design whereby interview and survey techniques were employed to gather the data. The flood-prone public elementary schools in the region near Agusan River were the target locales of the study. Aside from surveys, a non-probability sampling design was also utilized particularly purposive sampling in determining the participants of the interviews. The school principals as the SDDR chairpersons, SDDR coordinators, School-Based Feeding Program (SBFP) coordinators, Wash in Schools (WINs), and school health officers were the participants in each FPPES. Butuan City, Bayugan City, Cabadbaran City, Agusan del Norte, and Agusan del Sur school divisions were included as division participants of the study. The data were gathered using a checklist developed based on the Health and Safety Induction Checklist by Safety Culture Staff (2017). Frequency distribution was utilized in identifying the demographic profile of the participants and in determining the health risk management practices of schools. Based on the interviews, three challenges were identified by the informants, and they include diseases acquired during and after the flood, pest infestations during and after the flood and lack of comfort rooms with clean water supply. The spread of diseases such as respiratory, skin, mosquito-causing, and parasitic worm illnesses was among the health issues mentioned by the informants.